More than just a name? From magnetic to optical skyrmions and the topology of light - Jian Chen; Andrew Forbes; Cheng-Wei Qiu (Light: Science & Applications)
Abstract Topology is usually perceived intrinsically immutable for a given object. We argue that optical topologies do not immediately enjoy such benefits. Using ‘optical skyrmions’ as an example, we show that they will exhibit varying textures and topological invariants (skyrmion numbers), depending on how to construct the skyrmion vector when projecting from real to parameter space. We demonstrate the fragility of optical skyrmions under a ubiquitous scenario--simple reflection off an optical mirror. Optical topology is not without benefit, but it must not be assumed.